Evolution of spatial light modulator for high‐definition digital holography. Issue 1 (19th January 2019) - Choi, Ji Hun; Pi, Jae‐Eun; Hwang, Chi‐Young; Yang, Jong‐Heon; Kim, Yong‐Hae; Kim, Gi Heon; Kim, Hee‐Ok; Choi, Kyunghee; Kim, Jinwoong; Hwang, Chi‐Sun
Abstract : Since the late 20th century, there has been rapid development in the display industry. Only 30 years ago, we used big cathode ray tube displays with poor resolution, but now most people use televisions or smartphones with very high‐quality displays. People now want images that are more realistic, beyond the two‐dimensional images that exist on the flat screen, and digital holography—one of the next‐generation displays—is expected to meet that need. The most important parameter that determines the performance of a digital hologram is the pixel pitch. The smaller the pixel pitch, the higher the level of hologram implementation possible. In this study, we fabricated the world‐smallest 3‐μm‐pixel‐pitch holographic backplane based on the spatial light modulator technology. This panel could display images with a viewing angle of more than 10°. Furthermore, a comparative study was conducted on the fabrication processes and the corresponding holographic results from the large to the small pixel‐pitch panels.